Implementation Character Building of Tolerance through Religious Moderation in Early Childhood Education Institutions - Apriani, Misna; Sari, Meilida Eka; Putra, Bramana Nanditya; Sari, Miya Rahmawati (Journal of Childhood Development, 2025)
This study aims to describe the implementation of character building of tolerance through religious moderation in Early Childhood Education (PAUD) institutions in Musi Rawas Regency. The research approach used is descriptive qualitative with research subjects consisting of teachers, principals, and parents of students in several PAUD institutions. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that the instillation of character building of tolerance through religious moderation is implemented through integrated learning with moderation values ​​such as mutual respect, appreciation of differences, cooperation, and empathy. Teachers act as role models and facilitators in shaping children's behavior through role-playing activities, storytelling, singing, and collaborative activities that foster a moderate attitude and mutual respect. Supporting factors for successful implementation include the commitment of teachers and principals, the support of a harmonious social environment, and the active role of parents. The main obstacles lie in teachers' limited understanding of the concept of religious moderation and the lack of supporting learning media. This study confirms that instilling a character of tolerance through religious moderation in PAUD institutions plays an important role in shaping a generation of children who are noble, peace-loving, and ready to live in diversity from an early age.